HISTORISITAS, SETTING SOSIAL, POLITIK, DAN KAKAKTER HUKUM ISLAM DI KALIMANTAN SELATAN - Zainal Muttaqin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
Since Islam was accepted as the official religion of the Banjar kingdom, since then Islamic law also influenced the system of social norms and state administration. In its history, the existence of Islamic law has experienced ups and downs that are strongly influenced by social and political factors that occur in the South Kalimantan region. The role of the ulama, especially Sheikh Muhammad Arsyad al-Banjari along with his descendants contributed greatly in shaping the contextual and localistic character of Islamic law. Which in some cases was different from what had been formulated by earlier jurists.